A proposal for a procedure to plan the production capacity of a company - Estevez-Torres, Ailen (2021)
The objective of this research was to design a procedure to plan the production capacity of a company. In order to develop the research, the direct observation, historical-logical, hypothetico-deductive and analytic-synthetic methods, as well as observation techniques, document reviews and surveys, were used. In addition, the Delphi method was applied to validate the procedure. The integration of positive aspects from eight of the consulted procedures and the inclusion of other aspects not addressed in the research were achieved. Moreover, production capacity planning is shown as a continuous improvement process.